Iron Cosmology, Slavery, and Social Control: The Materiality of Rebellion in the Coffee Plantations of the Paraíba Valley, Southeastern Brazil. (3rd May 2016) - Symanski, Luís Cláudio P.; Gomes, Flávio dos Santos
Abstract : Archaeological research carried out in the slave quarters of two coffee plantations in the Paraíba Valley, Southeastern Brazil, revealed a material scarcity that is highly contrastive with the material abundance found on slave quarters in sugar plantation regions. In this article, we first discuss the reasons for these differences, arguing that they are related to a tight control over the enslaved foodways. Although this control could have suppressed an important feature of the African cultural practices, we argue that these groups adopted other material resources that expressed values widely shared among the Central African societies from which most of them came. These items very likely recalled a general Central African cosmology regarding the role of iron and beliefs in supernatural powers associated with blacksmiths. In the final section, we discuss the crucial role that these belief systems played in the slave rebellions that arose in this region.